2022
DOI: 10.25304/rlt.v30.2803
|View full text |Cite
|
Sign up to set email alerts
|

Mixed reality results in vocational education: a case study with HoloLens 2

Abstract: Pedagogy in vocational education is challenged by the increasing availability of mixed reality (MR) technologies. Wearable technologies such as the Microsoft HoloLens are being embedded in nursing education programmes in Aotearoa New Zealand and Australia and explored in other subject areas such as construction, architecture, and engineering. Empirical research undertaken with staff and students in a nursing programme reinforces and expands on previous research findings about enhanced student motivation, learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similarly, a study by Park and colleagues found that AR can enhance literacy (Park & Khoshnevisan, 2019). Enhanced student motivation, learning, and engagement are some of the benefits of AR identified by researchers exploring its use in medicine, construction, architecture, and engineering (Adams et al, 2022). Learner's interaction with the virtual models in the AR environment is essential.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Similarly, a study by Park and colleagues found that AR can enhance literacy (Park & Khoshnevisan, 2019). Enhanced student motivation, learning, and engagement are some of the benefits of AR identified by researchers exploring its use in medicine, construction, architecture, and engineering (Adams et al, 2022). Learner's interaction with the virtual models in the AR environment is essential.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The availability of Mixed Reality (MR) technologies, such as wearable devices like the MicrosoftHoloLens, is challenging pedagogy in vocational education [7]. These technologies are being incorporated into nursing education programs and explored in other subject areas like construction, architecture, and engineering [7].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of Mixed Reality (MR) technologies, such as wearable devices like the MicrosoftHoloLens, is challenging pedagogy in vocational education [7]. These technologies are being incorporated into nursing education programs and explored in other subject areas like construction, architecture, and engineering [7]. While digital platforms have facilitated increased interaction between students and instructors, their development for complex project-based and open-ended education content is still incomplete [8].…”
Section: Introductionmentioning
confidence: 99%